2021
DOI: 10.3906/bot-2107-29
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content, antibacterial, antioxidant, and toxicological investigations of Erodium guttatum (Geraniaceae) collected from the Northeast of Morocco

Abstract: Erodium guttatum is a medicinal plant used traditionally to fight against some pathologies such as microbial infections. In fact, the aim of the present study was to evaluate the antibacterial and antioxidant activities of E. guttatum extracts in addition to their toxicity. To achieve the objectives of this study, methanol, and aqueous extracts of E. guttatum were prepared. Then, antibacterial activity was evaluated against Escherichia coli ATCC 25922,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The antioxidant activity of the two tested EOs was evaluated using the following three commonly used in vitro complementary assays: DPPH, H 2 O 2 , and xanthine oxidase (XO) methods, and following the same procedures as described previously by the research group [ 25 27 ]. Each assay was carried out in triplicate, and allopurinol and ascorbic acid were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant activity of the two tested EOs was evaluated using the following three commonly used in vitro complementary assays: DPPH, H 2 O 2 , and xanthine oxidase (XO) methods, and following the same procedures as described previously by the research group [ 25 27 ]. Each assay was carried out in triplicate, and allopurinol and ascorbic acid were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, studies have confirmed the richness of the extracts of E. guttatum in phenolic compounds. It has also been shown to have antioxidant activity by DPPH, H2O2, and xanthine oxidase assays [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant capacity of the MPEO, thyme honey and their mixture was evaluated through three well-established in vitro assays: DPPH●, H 2 O 2 , and xanthine oxidase (XO) tests, following the protocols established by the research team in previous studies [ [32] , [33] , [34] ]. Each experiment was repeated three times, using allopurinol and ascorbic acid as positive controls.…”
Section: Methodsmentioning
confidence: 99%